LOW DENSITY LIPOPROTEIN (LDL) LEVELS IN MALE ATHLETES, SMOKERS AND NON-SMOKERS AGED 17-20 YEARS - Yulia Ainur Rahma; Heri Purnama Pribadi (Journal of Strength and Conditioning, 2026)
Smoking is known to increase oxidative stress, disrupt lipid metabolism, and accelerate the formation of oxidized Low Density Lipoprotein (LDL). Conversely, regular physical exercise enhances antioxidant capacity and improves lipid regulation. The interaction between smoking habits and intense physical activity in young athletes is important, as both may influence lipid balance and LDL levels associated with atherosclerosis risk. This study aimed to determine differences in LDL levels between smoking and non-smoking athletes aged 17–20 years. This study used an analytical observational design with a cross-sectional approach. A total of 23 male athletes were divided into smoking and non-smoking groups. Blood samples were collected via venipuncture to measure LDL levels through laboratory analysis. Data normality was tested using the Shapiro–Wilk test. Since one group was not normally distributed, the Mann–Whitney test was applied with a significance level of 0.05. Smoking athletes had a higher mean LDL level (107.10 ± 29.11 mg/dL) compared to non-smoking athletes (86.02 ± 20.34 mg/dL). However, statistical analysis showed no significant difference between the groups (p > 0.05). Descriptively, there was a tendency toward higher LDL levels in smoking athletes, although all values remained within ranges potentially influenced by regular physical activity. moking habits in young athletes did not show a significant effect on LDL levels. This may be due to physiological compensatory mechanisms induced by regular physical training, which can mitigate the negative effects of smoking on lipid metabolism.